Intensity of fatty oxidative processesfractions of blood sausages - Strashynskyi, Igor; Fursik, Oksana; Stelmakh, Valeriia (My University, 2021)
Iron deficiency is one of the most common pathologies of modem humanity. According to the WHO, iron deficiency is observed in more than 1.5 billion people, including about 500 million people with iron deficiency anemia.
Keywords: кафедра технології м’яса і м’ясних продуктів; blood sausages; oxidative processesfractions; iron deficiency